Świętość powołania małżeńskiego - Pązik, Tomasz (Społeczeństwo, 2022)
In its teaching, the church emphasizes its great „yes” to life, which should be echoed in every marriage. That is why you cannot confuse natural family planning with contraception, or talk about it as a decent method of contraception, acceptable by the Church, because then unfortunately the attitude of contraconception in human consciousness strengthens.